Pengaruh Efikasi Diri dan Kesiapan Belajar terhadap Hasil Belajar Mata Kuliah Perencanaan Pembelajaran dan Microteaching dengan Motivasi Belajar sebagai Variabel Intervening - Tirta, Bayu; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the influence of self-efficacy and learning competency on students’ learning outcomes in the Learning Planning and Microteaching course, both directly and through learning motivation as an intervening variable. The research also explores how self-efficacy and learning readiness affect students’ motivation to learn and how this motivation contributes to improved learning outcomes. This quantitative study involved 69 students of the Automotive Engineering Education Program at Semarang State University and was conducted from January to September 2025. Data were collected using a questionnaire and analyzed with SmartPLS 4, including tests of validity, reliability, R-square, F-square, and Goodness of Fit (GoF). The results revealed that hypotheses H2, H4, H5, H6, and H7 were accepted with significance values below 0.05, indicating significant relationships among the tested variables. Specifically, self-efficacy significantly affected learning motivation, while learning readiness had a significant impact on both motivation and learning outcomes through the mediating role of learning motivation. The GoF value of 0.684 indicates that the model demonstrates a strong overall fit, suggesting that the combined outer and inner model performance is in the high category. These findings highlight the essential role of motivation as a bridge between self-efficacy, learning competency, and academic achievement in vocational teacher education.